Natural Hazards Reconnaissance With the NHERI RAPID Facility - Berman, Jeffrey W.; Wartman, Joseph; Olsen, Michael; Irish, Jennifer L.; Miles, Scott B.; Tanner, Troy; Gurley, Kurtis; Lowes, Laura; Bostrom, Ann; Dafni, Jacob; Grilliot, Michael; Lyda, Andrew; et al. (Frontiers in Built Environment, 2020)
In 2016 NSF funded an interdisciplinary multi-institutions team to develop and operate the Natural Hazards Reconnaissance Facility (known as the “RAPID”) as part of the Natural Hazards Engineering Research Infrastructure (NHERI) program. To enable support of state of the art natural hazard reconnaissance research, the RAPID facility’s instrumentation portfolio and operational plan were developed over the following two years. Input was gathered from the natural hazards engineering community, the facility’s leadership, the National Science Foundation, and an interdisciplinary, external steering committee of scientists with decades of reconnaissance-based research experience in natural hazards and disasters. Beginning operations in September 2018, the RAPID now provides instrumentation, software, training, and support services to investigators performing field-based research before, during, and after natural hazards. Since beginning operations, RAPID has supported the data collection efforts of more than 40 missions. Applications have ranged across disciplines and hazards. They have also included data gathering in large-scale experimental facilities. These activities have produced an unprecedented amount of high-quality field data sets that are archived on the DesignSafe cyberinfrastructure platform. This paper describes the development of the RAPID facility, the equipment portfolio, and services provided by RAPID, including a custom-built reconnaissance software platform called RApp, and the opportunities RAPID provides for user training. Additionally, overviews of three example deployments of the RAPID equipment and data collection services are described; descriptions include the field data collection processes, the resulting high-quality data sets, and the impact of the data and resulting research on natural hazard resilience.